Labor Market Laws and Intra-European Migration: The Role of the State in Shaping Destination Choices - John Palmer; Mariola Pytlikova (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
This article investigates the relationship between migrants' destination choices and the formal labor market access afforded by multiple potential host countries in the context of the EU's eastward enlargement. We use an index of labor market access laws combined with data on migration from new EU member states into the existing states of the EU and EFTA from 2004 through 2010 to test whether (1) migrants are attracted to destinations that give them greater formal labor market access, and (2) migration flows to any given destination are influenced by the labor market policies of competing destinations. Our data support both propositions: Migration between origin/destination pairs was positively associated with the loosening of destination labor market restrictions while negatively associated with the loosening of competing destinations' labor market restrictions. These relationships hold even when economic indicators, social welfare spending, and existing immigrant stocks are modeled. By combining rich EU data with a unique approach to evaluating competing legal regimes, the analysis helps us better understand how law shapes migration in a multi-destination world.
Keywords: 330